Relative remoteness and wage differentials in the Canadian allied health professional workforce - Neeru Gupta; Adrienne Gulliver; Paramdeep Singh (James Cook University, 2023)
Introduction: Health workforces around the world are characterized with geographic maldistribution, often leading to inequalities in rural health outcomes. Monetary incentives are frequently raised as a policy option to bolster recruitment of healthcare practitioners to rural and underserved communities; however, few rural health workforce studies focus on allied health professionals (AHPs), include urban comparators, integrate gender considerations, or measure rural diversity. This population-based observational study examines trends in the geographic and gender distribution and earnings of AHPs in Canada across the rural-urban continuum. Methods: Nationally representative data from the 2006 and 2016 Canadian population censuses were pooled and linked with the geocoded Index of Remoteness for all inhabited communities. Five groups of university-educated AHPs providing prevention, diagnostic evaluation, therapy, and rehabilitation services were identified by occupation. Multiple linear regression models were used to estimate the associations between relative remoteness and annual earnings of AHPs aged 25-54 years, controlling for gender and other personal and professional characteristics. Results: The density of AHPs was found to be 15 times higher in more urbanized and accessible parts of the country (23.6-25.6 per 10 000 population in 2016) compared to the most rural and remote areas (1.6 per 10 000 population), a pattern that changed little over the previous decade. A positive correlation was seen across occupations in terms of the degree of feminization and their geographic dispersion by relative remoteness. While pharmacists residing in more rural and remote communities earned 9% (95% confidence interval 4-15%) more than those in core urban centers, relative remoteness contributed little to wage differentials among dentists, physiotherapists and occupational therapists, or other AHPs in therapy and assessment (no significant difference at p<0.05). Women earned significantly less than men in dentistry, pharmacy, and physical or occupational therapy, after adjusting for remoteness and other characteristics. Conclusion: This study did not find consistent wage disparities by relative remoteness as characterizing allied health professions in Canada. The evidence base to support financial incentives to AHPs to reduce perceived opportunity costs associated with working and living in rural and underserved areas remains limited. More research is needed on the intersections of rurality, gender, and wage differentials among AHPs in different national contexts.